Polarization networks around the SDGs in the press from 2020 to 2023 - García Lirios, Cruz; Crespo, Julio E.; Sepulveda, Juan Masilla; Gracia, Tirso Javier Hernandez (Heritage and Sustainable Development, 2024)
Polarization in the media is a phenomenon classified as ambivalent and volatile because radical positions change to moderate and neutral. The objective of the study was to demonstrate this process in press releases and expert evaluations regarding the Sustainable Development Goals (SDG). A documentary, cross-sectional, exploratory, and retrospective work was carried out with a sample of press releases with national circulation and published from 2020 to 2023 headed with SDGs. The results verify the null hypothesis of significant differences between the theoretical structures concerning the empirical observations. The scope and limits of the study are discussed, as well as a local risk communication policy.